Pengaruh Perputaran Kas, Loan To Deposit Ratio (Ldr), Biaya Operasional Pendapatan Operasional (Bopo) Dan Total Asset Turnover (Tato) Terhadap Profitabilitas (Studi Kasus Pada Lembaga Keuangan Syariah Yang Terdaftar Di Bei 2015-2019) - Mohammad Ainul Yaqin; Jeni Susyanti; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis current study aimed to empirically examine the effect of Cash Turnover, Loan to Deposit Ratio (LDR), Operating Cost Operating Income (OCOI) and Total Asset Turnover (TATO) on the Profitability of Islamic Financial Institutions which is listed on Indonesia Stock Exchange from 2015 to 2019. The sample of this study was obtained by using a purposive sampling method. Based on the criteria, 48 samples were gained to be the research subjects. The data analysis and technique used in this study was Multiple Linear Regression Analysis. The results of the study revealed that the variable of Cash Turnover has a negative significant effect on Profitability, Loan to Deposit Ratio (LDR) has no effect on Profitability, Operating Cost Operating Income (OCOI) has a negative significant effect on Profitability, and Total Asset Turnover (TATO) has a positive significant effect on Profitability. Keywords: Profitability, Loan to Deposit Ratio (LDR), Operating Cost Operating Income (OCOI), Total Asset Turnover (TATO), Profitability.